Manfaat Sirih Merah (Piper crocatum) sebagai Agen Anti Bakterial terhadap Bakteri Gram Positif dan Bakteri Gram Negatif - Rachmawaty, Farida Juliantina; Mahardina, Dewa Ayu Citra; Nirwani, Bunga; Nurmasitoh, Titis; Bowo, Endrawati Tri (Faculty of Medicine, Universitas Islam Indonesia, 2009)
Background of choosing the subject: In recent years world society including Indonesia tend to consider the use of herbal medicine - back to nature. The advantages of herbal medicine become an interesting discussion. Most information expand in society is empirical rather than scientific evidence. Thus red betel vine's benefit also becomes interesting discussion but evidence based medicine about it is very little. The purpose of this study is to know the potency of antibacterial power of ethanol extract of red betel vine (Piper crocatum) toward gram positive and gram negative bacteria. Research Methodology: This research was laboratory experimental study. The extract of red betel vine was made with standard ethanol solvent. This extract was examined in Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 35218. Experimental method is serial dilution. Result was analyzed descriptively with Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The examination in each bacterium was repeated 5 times. Result: The result shown that ethanol extract of red betel vine (Piper crocatum) has ability to inhibit the growth of Gram positive (Staphylococcus aureus) and to kill it on concentration 25%. While the ability to inhibit the growth of Escherichia coli (Gram negative) on 6,25% (visual observation and after has been planted in Mc Conkey media). From result repetition in 5 times, gram negative is more stable rather than gram positive. Conclusion: The ethanol extract of red betel vine (Piper crocatum) has antibacterial effect toward Gram positive and gram negative. MIC and MBC Staphylococcus aureus at 25% while for MIC and MBC Escherichia coli at 6,25%.Keywords: antibacterial – Red betel vine – Piper crocatum – Staphylococcus aureus – Escherichia coli